Effect of administering ovsynch protocol plus postbreeding infusionon first service pregnancy outcome in cows - Yildiz, Atilla (My University, 2010)
The objectives were to determine the effect of ovsynch plus postbreeding infusion treatment combined with fixed time AI on pregnancy rate in healthy Holstein cows. A total of 36 cows ageing between three and eight were used. Cows were were randomly assigned to one of three treatment groups. Cows (n = 12) in first group (control) received no treatment; they were managed as healthy cows and inseminated at the first estrus after the voluntary waiting period. Second group (n = 12) received ovsynch protocol. Ovsynch protocol included administration of GnRH (2.5 mL im, Receptalfi, 0.004 mg Buserelm mL-1, Intervet) on dayl, administration of PGF2a analogse D-Cloprostenol (2 mL im, Dalmazin, 0.075 mg D-Cloprostenol mL-1, Vetas) on day 8 and second GriRH administration on day 10. Animals in this group were artificially inseminated 18 h following 2nd GnRH administration. Third group (n = 12) received ovsynch but with the addition of 500 mg of Gentamycin sulphate (10 mL added to 30 mL of saline iu, Gentavet, 50 mg Gentamycin sulphate mL, Veta§) in 30 mL of saline by intrauterine infusion 2 h after artificial insemination. Pregnancy diagnosis was performed via rectal palpation 45 days post insemination. Pregnancy rate in the cows that received Ovsynch + Postbreeding infusion was higher (p<0.05) than that of cows synchronized with ovsynch. Based on the odds ratio, pregnancy rate for cows treated with Ovsynch + Postbreeding infusion increased 2.8 folds (Odds Ratio (OR): 2.80 (0,532-14,7355) 95% Confidence Interval (CI)) when was compared with control group and 6 folds (OR: 6.00 (1.0177-35.3753) 95% CI) when was compared with ovsynch group. The results of these studies indicate that acceptable pregnancy rates can be achieved in the recipients that have received the ovsynch plus postbreeding infusion protocol without the necessity of estrus detection. © Medwell Journals, 2010.
Keywords: Cow; Ovsynch; Postbreeding infusion; Pregnancy rate; Timed artificial insemination; Turkey